Comparative Analysis of Volatile Oils from Lonicera japonica Thunb. var. chinensis wakey by HS-SPME and GC-MS - Wang, Dai-Jie; Shu, Xi-Kai; Zhao, Xian-En; Wang, Xiao; Li, Sheng-Bo; Du, Jin-Hua (Asian Journal of Chemistry, 2012)
The volatile oils of the flowering stages, i.e., the flower bud stage, silver flowering stage, gold flowering stage as well as the leaf from Lonicera japonica Thunb. var. chinensis wakey were extracted and analyzed by headspace solid-phase microextraction and GC-MS. In this study, Lonicera japonica Thunb. was used as contrastive species. The fiber coating of 65 μm PDMS/DVB was chosen to extract the volatile oils. A total of 46, 50, 51 and 20 volatile compounds were identified, constituting of 98.16, 97.31, 95.99 and 97.84 % of oil composition of the flower bud stage, silver flowering stage, gold flowering stage and leaf from L. japonica var. chinensis wakey, respectively. The dominant constituents of the above parts were hydrocarbons (37.79 %), oxygenated monoterpenes (28.98 %), alcohols (25.44 %) and esters (53.29 %). It is concluded that the esters in flowering period contributed to the attractive aroma of L. japonica var. chinensis wakey.